Keep Them Safe: Evaluation framework - Bromfield, L; McDonald, M; Valentine, K; McHugh, M; Hilferty, F; Katz, I; Adamson, E; Edwards, B; Gray, M (My University, 2010)
The framework is designed to establish consistent reporting requirements from key components of the action plan to assess the extent to which the plan has met its objectives of improving the safety, welfare and wellbeing of children in NSW, why aspects of the reform have been successful or not, and processes for using the evaluation outcomes to adjust future approaches based on progressive evaluation findings. A key challenge in developing an evaluation framework for KTS is the breadth and complexity of the initiative. The overall objective is an improvement in the wellbeing and safety of all children in the child welfare system, but improvements are anticipated in service integration and delivery in the primary, secondary and tertiary service systems, so that families receive better, and better-targeted, services when they need them.
Keywords: Health and wellbeing; Health and wellbeing